DIFFERENCES IN WALKING BALANCE ACROSS BODY MASS INDEX ANDFALL RISK CATEGORIES AMONG OLDER ADULTS - Nur Rachmat; M Syafii; Anissa Eka Septiani; Tarezza Dewi Sekar Mayang; Indra Yulianti (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
This study aimed to examine differences in walking balance across body mass index (BMI) categories and fall risk categories among community-dwelling older adults. Methods: A cross-sectional study was conducted involving 55 older adults aged 50–90 years in a community setting in Central Java, Indonesia. Body mass index was classified using Asia–Pacific criteria. Fall risk was assessed using the Morse Fall Scale, and walking balance was evaluated using the 8-Foot Up and Go test, categorized as balanced or impaired. Data were analyzed using descriptive statistics and Pearson’s chi-square test. Results: The mean age of participants was 63.16 ± 8.60 years, and the mean BMI was 22.02 ± 3.86 kg/m². Overall, 69.1% of participants exhibited impaired walking balance. No significant association was found between BMI category and walking balance status (χ² = 4.78, p = 0.188). In contrast, fall risk category showed a significant association with walking balance status (χ² = 11.61, p = 0.003), with higher fall risk corresponding to greater balance impairment. Conclusion: Walking balance impairment among older adults was significantly associated with fall risk category but not with BMI classification. These findings indicate that fall risk assessment provides greater clinical relevance for identifying balance impairment than anthropometric measures alone.